2021
DOI: 10.32479/ijefi.10857
|View full text |Cite
|
Sign up to set email alerts
|

Real Exchange Rate and Trade Balance Dynamics in Cote D’ivoire

Abstract: This study examines the relationship between real exchange rate and trade balance in Cote d'Ivoire during the period from 1975 to 2017. The study employs the ARDL bounds testing approach to cointegration developed by Pesaran et al. (2001) in the examination of this nexus. Cointegration analysis and error correction modeling are used to determine the long run as well as short run dynamics, between real exchange rate and trade balance. The empirical results show negative and significant effects of domestic incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…The opposite is also true, namely that a depreciation of the real exchange rate is a stimulating factor for exports. This confirms the work of Yaya (2021) for the Côte d’Ivoire according to which a depreciation of real exchange rate causes an improvement in the trade balance in a significant way both in the short and long run in this country. However, this is in contrast to the results of Lucy and al .…”
Section: Resultssupporting
confidence: 84%
“…The opposite is also true, namely that a depreciation of the real exchange rate is a stimulating factor for exports. This confirms the work of Yaya (2021) for the Côte d’Ivoire according to which a depreciation of real exchange rate causes an improvement in the trade balance in a significant way both in the short and long run in this country. However, this is in contrast to the results of Lucy and al .…”
Section: Resultssupporting
confidence: 84%
“…He found that foreign direct investment and trade openness have negative effects on the trade balance, whereas the exchange rate is insignificantly related to the trade balance. In a recent study, Keho (2021) found a positive effect of the real exchange rate depreciation and a negative effect of domestic income on the trade balance in Cote d'Ivoire.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The evidence from this literature is mixed and conflicting. Some studies found that depreciation of real exchange rate has a significant improving effect on trade balance (Baharumshah, 2001;Bahmani-Oskooee, 2001;Boyd et al, 2001;Kale, 2001;Lal & Lowinger, 2002;Musila & Newark, 2003;Yol & Baharumshah, 2007;Igue & Ogunleye, 2014;Anning et al, 2015;Caporale et al, 2015;Ogbonna, 2016;Hunegnaw & Kim, 2017;Ousseini et al, 2017;Sokeng Dongfack & Ouyang, 2019;Yazgan & Ozturk, 2019;Keho, 2021a), while others reported that depreciation worsens trade balance (Onafowora, 2003;Adeniyi et al, 2011;Genemo, 2017). Still, others failed to establish any significant relationship between the two variables (Hatemi-J & Irandoust, 2015;Duasa, 2007;Loto, 2011;Akpansung & Babalola 2013;Shawa & Shen, 2013;Meniago & Eita, 2017;Kamugisha & Assoua, 2020).…”
Section: Introductionmentioning
confidence: 99%